2009
DOI: 10.1086/646614
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral CXCR3‐Associated Chemokines as Biomarkers of Fibrosis in Chronic Hepatitis C Virus Infection

Abstract: The strong association between CXCR3-associated chemokines and fibrosis suggests that they may have promise as noninvasive markers of hepatic fibrosis in a predominantly white HCV genotype 1-infected population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
94
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 33 publications
10
94
2
1
Order By: Relevance
“…Comparing F2 and F4 patients the concentrations of IL-2R, IL-6, IL-8, CXCL9, CXCL10, CXCL12 and MIF were found statistically higher (with p<0.05) in chronic inflammation patients with F4 fibrosis grade in respect to F2 fibrosis grade . These data agreed with a recent paper reporting that CXCL9 and CXCL10 were significantly elevated in patients with advanced fibrosis (Zeremski et al 2009). …”
Section: Chronic Inflammation Patients With Different Fibrosis Stagessupporting
confidence: 93%
“…Comparing F2 and F4 patients the concentrations of IL-2R, IL-6, IL-8, CXCL9, CXCL10, CXCL12 and MIF were found statistically higher (with p<0.05) in chronic inflammation patients with F4 fibrosis grade in respect to F2 fibrosis grade . These data agreed with a recent paper reporting that CXCL9 and CXCL10 were significantly elevated in patients with advanced fibrosis (Zeremski et al 2009). …”
Section: Chronic Inflammation Patients With Different Fibrosis Stagessupporting
confidence: 93%
“…3 More than 50% of HCV cases remain asymptomatic in the initial phase, and are not diagnosed prior to onset of severe hepatic fibrosis. 4 HCV is therefore the leading cause of liver transplants in Europe and America. 3,5 Early detection of HCV and appropriate therapeutic management in chronic patients can prevent these complications and therefore improve patient health and reduce patient morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Pro-inflammatory cytokines and chemokines are involved in this process and plasma levels of these may be associated with different stages of hepatitis C associated liver fibrosis [9;10]. Although current knowledge about these inflammatory cytokines and chemokines is limited, studies have demonstrated that plasma levels of some chemokines correlate with liver fibrosis [11][12][13]. There is a need for non-invasive, simple, inexpensive and accurate tools to determine and monitor liver fibrosis in CHC patients.…”
Section: Introductionmentioning
confidence: 99%